The potential of cannabinoids in managing cancer-related anorexia in older adults: a systematic review of the literature - Chiara Ceolin; Marina De Rui; Adele Ravelli; Mario Virgilio Papa; Maria Devita; Giuseppe Sergi; Alessandra Coin (Elsevier, 2024)
Background and objectives: Anorexia of aging (AoA) is a prevalent geriatric syndrome characterized by a multifactorial decline in appetite and reduced food intake associated with the aging process. This systematic review aims to investigate the use and outcomes of cannabinoids in addressing AoA, with the goal of providing a comprehensive understanding and discussing their potential integration into daily clinical practice. Methods: A thorough search of databases (Embase Ovid, Scopus, PubMed, Cochrane Library, and Web of Science) identified 6100 studies. After eliminating duplicates and screening titles and abstracts, 25 studies underwent full appraisal. Two reviewers assessed inclusion suitability, and study methodologies were evaluated using the Newcastle-Ottawa Scale (NOS) for observational studies and the modified Jadad Scoring Scale for randomized controlled trials. Ultimately, six studies published between 2002 and 2019, involving 869 participants, were included in the review. Results: Out of the 6 fin. l papers selected, 5 were randomized trials, and 1 was a prospective study. Megestrol acetate (800 mg/d) proved to be more effective than dronabinol 2.5 mg twice a day in increasing appetite. Nabilone (at a dosage of 0.5 mg per day) did not show superiority over placebo in alleviating symptoms such as pain, nausea, loss of appetite, and weight. However, with a double dosage followed by 1.0 mg/6 weeks, after eight weeks of treatment, patients recorded a significant increase in calorie intake and carbohydrate consumption compared to the placebo group, with some patients also experiencing substantial weight gain. Regarding delta-9-tetrahydrocannabinol (THC), a weight increase of ≥10% was observed in 17.6% of patients with doses of 5 mg or 10 mg capsules daily, without significant side effects. Additionally, patients treated with THC 2.5 mg reported improved chemosensory perception and increased appetite before meals compared to placebo. No significant side effects were reported in older adults taking cannabinoids. Conclusions: Cannabinoids offer promise in enhancing the quality of life for older individuals with active neoplastic disease. However, to establish comprehensive guidelines, further research with larger sample sizes is essential. Only through this approach can we fully grasp the potential and application of cannabinoids in addressing the nutritional concerns associated with neoplastic diseases.